Determination of the mutant allele frequency in patients with neurofibromatosis type 2 and somatic mosaicism by means of deep sequencing. Issue 8 (29th May 2015) - Spyra, Melanie; Otto, Benjamin; Schön, Gerhard; Kehrer‐Sawatzki, Hildegard; Mautner, Victor‐Felix
<x xml:space="preserve">Abstract</x> Neurofibromatosis Type 2 (NF2) is an autosomal disorder caused by mutations of the NF2 gene. More than half of all NF2 patients have unaffected parents and carry de novo mutations, which may be of prezygotic or postzygotic origin. The latter can result in mosaicism, which is relatively common in NF2 patients. Previous studies indicated that, in 50% of patients with mosaic NF2 mutations, the mutant allele is only detectable by Sanger sequencing of PCR products amplified from tumor tissue but not from blood samples. In order to establish a highly sensitive method that has the power to detect low levels of NF2 mutant alleles from blood samples of mosaic NF2 patients, we performed ultra deep sequencing and calculated the percentage of mutant and wildtype NF2 alleles. The mutant allele frequencies detected ranged from 2.6% to 19.7%. In three patients, however, the NF2 mutation previously identified in tumor tissue was not identified in blood samples by means of deep sequencing, suggesting absence of mutant cells in the blood. Remarkably, we observed a correlation between the age at onset of the disease and the mutant allele frequency. Our study indicates that ultra deep sequencing is an effective and highly sensitive method to determine the mutant allele frequency in patients with mosaic NF2 gene mutations, which enables extended phenotype/correlations in these patients. © 2015 Wiley Periodicals, Inc.